Aflatoxigenic Aspergilli in foods and feeds in Uganda - Sebunya, Teresa K.; Yourtee, David M. (Journal of Food Quality, 1990)
Studies conducted during the sixties and the seventies on food crops in Uganda showed that the populace was exposed to consumption of aflatoxin-contaminated foods. These studies also linked the highest incidence of liver cancer in the world to the presence of high levels of aflatoxins in the food and beverages. After a lapse of a decade, it was of interest to investigate the occurrence of aflatoxins and aflatoxigenic fungi in staple Ugandan food crops and poultry feeds derived from these foodstuffs. A simple, rapid and reproducible procedure was used. The procedure consisted of growing or culturing feed grains on a selective medium, Aspergillus flavus/parasiticus agar (AFPA) followed by screening for aflatoxin producing fungi on a coconut agar medium (CAM) under UV light with a subsequent confirmatory screening method for aflatoxin production by the fungi in pure culture. Fifty-four samples consisting of corn and peanuts, soybean and poultry feed were analyzed for content of aflatoxigenic. A. flavus/parasiticus and 25 of the samples were also screened for aflatoxins B1 and G1, zearalenone, sterigmatocystin, ochratoxin A, citrinin, vomitoxin, and diacetoxyscirpenol (DAS). Aflatoxigenic A. flavus/parasiticus was detected from the majority of corn (77%), peanuts (36% human food and 83.3% animal feed) and poultry feed (66.6%). but not from soybean samples. Two samples out of 25 contained detectable levels of aJatosin B, (20 ppb). For the jirst time other mycotoxins, zearalenone (3 samples) and vomitoxin (2 samples) were detected in corn from Uganda.
Keywords: Aflatoxigenic Aspergilli; Foods and feeds